Visual Assessment of Native Species Replacement Candidates for the Acacia Tree (Albizia saman) in the U.P. Diliman Academic Oval Streetscape - Gozon, Patrick Andrew E. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 5, 2016)
The acacia tree, botanically known as Albizia saman, has remained an integral element of the University of the Philippines Diliman campus landscape for almost seven decades (as claimed in the University of the Philippines websitehttp://www.upd.edu.ph/sitesofinterest.html). In 2009, a university wide memorandum was passed limiting the planting of exotic tree species in all U.P. campuses. Since A. saman is an introduced species from the Americas and not native to the Philippines, it is debated what species could be used to replace the acacia trees in the academic oval in case specimens die or are fallen. The study attempts to evaluate 14 native tree species already found growing within the U.P. Diliman campus as candidates to succeed the acacia trees as main street tree around the academic oval. The acacia is first scrutinized of its aesthetics based on the quality of space it creates in the campus landscape design. The candidate native tree species are then subjected to the same evaluation process and measured whether they could approximate Albizia saman’s design importance in U.P.’s unique urban landscape.